Pembentukan Identitas Korporat PT Kompas Media Nusantara sebagai Penyedia Konten (Content Provider) Televisi Lokal Pertama di Indonesia - Olivia Lewi Pramesti (Program Studi Ilmu Komunikasi, 2011)
Communication technology development has affected media industry. This condition forces media industry to adapt in order to keep them in the competition. Media industry now should operate in multi-platform basis. In corporate theme, one challenge that media should answer is building new corporate identity. The steps to build corporate identity are defining problem, planning and organizing the direction, acting and communicating, and program evaluation. This paper is discussing how PT Kompas Media Nusantara build their corporate identity in television industry. The brand Kompas is well-known as a daily newspaper. By 2011, Kompas held their own television stadion named KompasTV. This paper consist of four parts. First is introduction, describes about KompasTV and the media shake-up phenomenon in Indonesia. Second is literature review consists of corporate communication and corporate identity. Third is discussion about how KompasTV build their corporate identity. The fourth part is conclusion.